Interest Groups in U.S. Local Politics - Anzia, Sarah (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
Interest group scholarship has so far focused mainly on national politics and has had very little to say about interest groups in American cities, counties, school districts, and special districts. Initially published as a special issue in Interest Groups & Advocacy, this volume is a step toward remedying that by examining some of the interest groups that are commonly active in US local politics. The contributions herein discuss real estate developers, tenant organizations, teachers' unions, police unions, and local PACs-covering topics such as how they are organized, how they engage in local politics, some of the constraints on their influence, and the nuanced ways in which ideology and identities can sometimes shape what coalitions are possible in the local context. By bringing this work together in one place, in a volume devoted to research on interest groups, the hope is that this book will help to cement "interest groups in local politics" as the recognizable research focus it deserves to be. Sarah Anzia is Associate Professor of Public Policy & Political Science at University of California Berkeley, USA.
Chapter 1: Interest groups in US local politics: Introduction to the special issue -- Chapter 2: Developing a pro-housing movement? Public distrust of developers, fractured coalitions, and the challenges of measuring political power -- Chapter 3: Politics, power, and precarity: how tenant organizations transform local political life -- Chapter 4: Teachers' unions and school board elections: a reassessment -- Chapter 5: Interest groups, local politics, and police unions -- Chapter 6: PACs rule everything around me: how political action committees shape elections and policy in the local context -- Chapter 7: The age of urban advocacy.
Keywords: America -- Politics and government; Political planning; Elections; Legislation; American Politics; Public Policy; Electoral Politics; Legislative Politics